Distribution of (1,3)(1,4)-β-D-Glucans in Grains of Polish Oat Cultivars and Lines (Avena sativa L.) – Short Report - Sykut-Domańska Emilia; Rzedzicki Zbigniew; Zarzycki Piotr; Sobota Aldona; Błaszczak Wioletta (Polish Journal of Food and Nutrition Sciences)
The distribution of a fraction of soluble dietary fibre (1,3)(1,4)-β-D-glucans was depicted in selected Polish oat grains (Avena sativa L.). Localisation of β-glucans within the grains was visualised by the light microscopy with Calcofluor white as a fluorescence agent. The content of β-glucans varied in samples from 3.08% d.m. to 5.04% d.m. Analysis of distribution of (1,3)(1,4)-β-D-glucans showed that the localization of β-glucans varied between various cultivars and lines. It was demonstrated that the total content of (1,3)(1,4)-β-D-glucans in oat kernels had an effect on their distribution. All the lines and cultivars tested displayed the greatest accumulation of (1,3)(1,4)-β-D-glucans in the cells of the subaleurone layer. With increase in the levels of β-glucans in high-glucan oat cultivars and lines, a tendency was observed towards their greater accumulation in the central parts of the kernel. It makes oat grain particularly suitable for the production of wholemeal foods. It is important not only to focus on increasing the content of β-glucans, but also to investigate molecules distribution in the seed. It was also demonstrated that Dukat cultivar was characterised by an especially valuable triple aleurone layer, which makes this cultivar predestined for further breeding studies as an extremely valuable carrier of genetic information.